1997
DOI: 10.1073/pnas.94.22.12180
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between cytoplasmic dynein and dynactin is required for fast axonal transport

Abstract: Fast axonal transport is characterized by the bidirectional, microtubule-based movement of membranous organelles. Cytoplasmic dynein is necessary but not sufficient for retrograde transport directed from the synapse to the cell body. Dynactin is a heteromultimeric protein complex, enriched in neurons, that binds to both microtubules and cytoplasmic dynein. To determine whether dynactin is required for retrograde axonal transport, we examined the effects of anti-dynactin antibodies on organelle transport in ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(174 citation statements)
references
References 33 publications
9
162
1
2
Order By: Relevance
“…4C), and the inhibition was bidirectional (Fig. 4D), which is consistent with previous observations of decreased organelle motility with disruption of dynein/ dynactin function (21). The inhibition of vesicular transport along the microtubules by Htt antibodies suggests that Htt facilitates bidirectional vesicle motility.…”
Section: Resultssupporting
confidence: 80%
“…4C), and the inhibition was bidirectional (Fig. 4D), which is consistent with previous observations of decreased organelle motility with disruption of dynein/ dynactin function (21). The inhibition of vesicular transport along the microtubules by Htt antibodies suggests that Htt facilitates bidirectional vesicle motility.…”
Section: Resultssupporting
confidence: 80%
“…Second, that plus end motility is increased when minus-end motility is inhibited by incubation of vesicles with antibody to Kifc1 (Figure 8). These data are consistent with the possibility that these motors may be part of a yet to be elucidated protein complex that mediates their coordinate regulation, as has been suggested for vesicle-associated dynein and plus-end kinesins (Brady et al, 1990;Stenoien and Brady, 1997;Waterman-Storer et al, 1997;Ligon et al, 2004). This view is supported in the present study by the finding that Kifc1 and Kif5B can interact with each other as shown by immunoabsorption of native Kif5B by FLAGKifc1 expressed in 293T cells ( Figure 9B).…”
Section: Discussionsupporting
confidence: 80%
“…Dynactin activates dynein chains to couple organelles to microtubules for fast axonal retrograde transport (Waterman‐Storer et al ., 1997). Suppression of dynein impairs clearance of α‐synuclein aggregates via the autophagosome/lysosome pathway (Li et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%